Learning and the Language Art Membelajarkan Penguasaan Keterampilan Membaca dan Menulis pada Anak-Anak - Dwi Susanti, Rini (PIAUD Universitas Islam Negeri Sunan Kudus, 2013)
Children use language for social purposes so that teachers plan teachingactivities in the social component, such as classroom writing activities. The conceptof children’s language reflects the culture of their home community, so that theteachers must respect students’ language and appreciate the cultural differencesin their attitudes towards learning in general and learning language arts. Childrenlearn to read and write through the mastery of skills gradually. Their languagelearning is influenced by art learning where the language is given. Learningprograms should not be interpreted as any activity or material, but on the contrary,the teachers design the learning and teaching strategies form based on how thechildren learn. The approach used is cognitive learning theory, psycholinguisticsand sociolinguistics. In addition, it is in line with constructivist or cognitive